**Imax = Vmax / R** (*where R = inductive resistance XL)

**XL = ****ω*L ** (*where XL = inductive reactance , ω = angular frequency, L = inductance)

**ω = 2*pi*f **(*where f = frequency)

plugging **ω **back into equation for inductive reactance we get:

**XL = ****(2*pi*f) *****L **

Then plug this back in for **R **in the first equation for **Imax **and solve for **L:**

**Imax = Vmax / ****(2*pi*f) *****L **

so

**L = Vmax / Imax ****(2*pi*f)**

Part B:

you can find *ω* using the L from above and the previous equation:

**L = Vmax / Imax ****(2*pi*f)**

*ω = * **(2*pi*f)**

so

**L = Vmax / Imax****ω*

solving for *ω*

*ω *= Vmax / L*Imax (*where Imax is the new Imax given in Part B)